2020
DOI: 10.1167/jov.20.4.18
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous attention facilitates perceptual learning in visual acuity to untrained stimulus locations and features

Abstract: Visual perceptual learning (VPL) refers to the improvement in performance on a visual task due to practice. A hallmark of VPL is specificity, as improvements are often confined to the trained retinal locations or stimulus features. We have previously found that exogenous (involuntary, stimulus-driven) and endogenous (voluntary, goal-driven) spatial attention can facilitate the transfer of VPL across locations in orientation discrimination tasks mediated by contrast sensitivity. Here, we investigated whether ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 126 publications
(243 reference statements)
4
41
0
Order By: Relevance
“…In contrast, the Attention group showed VPL location transfer -similar d' improvement in both eyes at the trained and untrained diagonals. We found that spatial attention helps overcome location specificity, consistent with the few studies that have isolated the role of spatial attention during VPL and location transfer in neurotypical adults [28][29][30].…”
Section: Exogenous Attention Helps Overcome Location Specificity In Adults With Amblyopiasupporting
confidence: 89%
See 3 more Smart Citations
“…In contrast, the Attention group showed VPL location transfer -similar d' improvement in both eyes at the trained and untrained diagonals. We found that spatial attention helps overcome location specificity, consistent with the few studies that have isolated the role of spatial attention during VPL and location transfer in neurotypical adults [28][29][30].…”
Section: Exogenous Attention Helps Overcome Location Specificity In Adults With Amblyopiasupporting
confidence: 89%
“…Our training protocol successfully induced VPL. After training the amblyopic eye, both eyes of most observers in both groups exhibited similar performance improvements -higher d' and faster RTat the trained diagonal; training with attention did not potentiate the overall improvement at the trained diagonal, consistent with [28][29][30]. Our study contributes to a rich VPL literature in both neurotypical humans (reviews [1][2][3][4][5]) and those with amblyopia (reviews [10,12,[20][21][22][23]) demonstrating impressive neuroplasticity in the adult brain.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…However, subsequent learning of a new direction is faster (Liu and Weinshall, 2000), suggesting the involvement of some higher-level processes. Furthermore, the manipulation of higher cognitive control processes, such as endogenous covert attention or exogenous spatial attention, improves stimuli location transfer and visual perceptual learning transfer to untrained stimulus location and features, respectively (Donovan et al, 2020; Donovan and Carrasco, 2018). Visual improvements would then rely on the interaction between multiple cortical areas (Gilbert et al, 2001), the combination of local intrinsic circuits and feedback connections from higher order cortical areas (Dosher and Lu, 1998; Gilbert and Sigman, 2007).…”
Section: Introductionmentioning
confidence: 99%